2011
DOI: 10.1161/strokeaha.110.600288
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Improves Naming Reaction Time in Fluent Aphasia

Abstract: Background and Purpose-Previous evidence suggests that anodal transcranial direct current stimulation (A-tDCS) applied to the left hemisphere can improve aphasic participants' ability to name common objects. The current study further examined this issue in a more tightly controlled experiment in participants with fluent aphasia. Methods-We examined the effect of A-tDCS on reaction time during overt picture naming in 8 chronic stroke participants. Anode electrode placement targeted perilesional brain regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
227
2
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(253 citation statements)
references
References 7 publications
(8 reference statements)
12
227
2
6
Order By: Relevance
“…-Estabrooks, et al, 2005;Naeser, Martin, Nicholas, Baker, Seekins, Kobayashi, et al, 2005). Moreover, the results of our study are also consistent with previous evidence regarding the increased efficacy of daily combined rTMS or tDCS plus cognitive rehabilitation (Baker et al, 2010;Fiori et al, 2011;Floel et al, 2011;Fridriksson et al, 2011;Kakuda, Abo, Uruma, et al, 2010;Kang et al, 2011;Martin, Naeser, Ho, Treglia, et al, 2009;Weiduschat et al, 2011). The present study provides additional evidence supporting the use of combined behavioural and brain stimulation approaches to achieve successful outcomes in aphasia therapy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…-Estabrooks, et al, 2005;Naeser, Martin, Nicholas, Baker, Seekins, Kobayashi, et al, 2005). Moreover, the results of our study are also consistent with previous evidence regarding the increased efficacy of daily combined rTMS or tDCS plus cognitive rehabilitation (Baker et al, 2010;Fiori et al, 2011;Floel et al, 2011;Fridriksson et al, 2011;Kakuda, Abo, Uruma, et al, 2010;Kang et al, 2011;Martin, Naeser, Ho, Treglia, et al, 2009;Weiduschat et al, 2011). The present study provides additional evidence supporting the use of combined behavioural and brain stimulation approaches to achieve successful outcomes in aphasia therapy.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the treatment effect persisted for at least 1 week after treatment. Fridriksson et al (2011) applied the same procedure used by Baker et al (2010) in eight left-brain-damaged patients with chronic fluent aphasia, and showed that anodal tDCS administered during language treatment decreased verbal reaction times during naming, as assessed immediately post-treatment and 3 weeks later. Another recent study (Fiori et al, 2011) highlights the beneficial effects of 5 days of anodal tDCS in three aphasic patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcranial electrical stimulation is a versatile tool to modulate brain activity (Nitsche and Paulus 2000;Fregni et al 2006;Fecteau et al 2007;Fridriksson et al 2011). In vivo and in vitro studies have demonstrated that electric fields, whose amplitude is comparable to the one expected in tDCS, can modulate firing rate (Chan and Nicholson 1986), spike timing (Radman et al 2007), and the magnitude of synaptic responses (Kabakov et al 2012;Rahman et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration of the fact that functional and structural plasticity can be elicited even by short-term training in adults [40,41] has spurred the search for the underlying neuronal mechanisms [42] and potential interventions to facilitate them [43][44][45]. OI does not allow assessment of structural changes but has been successfully used to address the question of whether functional activation patterns may be used to track functional reorganization after stroke.…”
Section: (D) Guiding Rehabilitation After Strokementioning
confidence: 99%